Accessibility for Physical Disabilities People to engage with Transjakarta Bus: (Case Study on Seskoal and Tirtayasa Corridors of South Jakarta) (International Journal of Psychosocial Rehabilitation, 2020)
People with disabilities are part of Indonesian society who could acquire the same position, rights, and obligation as other Indonesian people in their lives and livelihoods. Therefore, the government policy should consider and accommodates disability rights in the community. The term people with disabilities, previously known as people with disabilities, but the latest development of the National Commission on Human Rights and the Ministry of Social Affairs views the term protection in the Indonesian perspective which has a negative connotation and is incompatible with the foundation of human rights with the noble values ​​of the nation that uphold human dignity. Therefore, agreeing to the term disability is replaced by the term disability. This has also been supported by the issuance of Law Number 8 of 2016 concerning Persons with Disabilities. Based on the description in the background of the problem above, a number of problems were formulated as follows: 1. How is the implementation and fulfillment of the people with physical disability rights to engage with the Transjakarta bus? 2. What are the factors that influence public administration related to accessibility for persons with physical disabilities in the Transjakarta bus transportation mode? The theory used by the authors in this study uses the theory of equality before the law as adopted by Article 27 paragraph (1). It is agreed, everyone agrees equally before the law. Equality before the law in the simplest sense is that all people are equal before the law.